Technology in rail transport management - Ranade, Prabha Shastri (Hyderabad : Icfai University Press, 2010)
Contributed articles predominantly with reference to India.
section 1. Global overview -- section 2. Indian scenario -- section 3. Metro rails in Indian cities.
"Icfai books."
Includes bibliographical references and index.
Keywords: Railroads -- Technological innovations; Railroads -- Technological innovations -- India; Railroads, Elevated -- Technological innovations -- India